Adverse Selection as a Barrier to Achieving Universal Public Health Insurance Coverage in China - Yang P; Zhong S; Wang X; Zhong R (Risk Management and Healthcare Policy)
Panxu Yang,1 Siqi Zhong,2 Xiangping Wang,1 Renyao Zhong1 1School of Public Management, East China Normal University, Shanghai, People’s Republic of China; 2Faculty of Business and Economics, University of Melbourne, Melbourne, AustraliaCorrespondence: Renyao Zhong, School of Public Management, East China Normal University, No. 3663, Zhongshan North Road, Putuo District, Shanghai, 200062, People’s Republic of China, Email ryzhong297@hotmail.comIntroduction: A significant presence of adverse selection in the health insurance market will pose a problem to achieving universal coverage. Public health insurance (PHI) in China is currently facing the challenge of declining enrollments. This situation aligns with the market failure scenario predicted by adverse selection theory.Methods: This study’s research sample comprises individuals who are freelancers, self-employed, those who are not actively employed, elderly persons not engaged in employment, and students aged 16 and above. Data from the 2020 wave of the China Family Panel Studies (CFPS) was used to investigate the presence of adverse selection in China’s PHI. Logit models were used to analyze the relationship between hospitalization and the decision to enroll in PHI while adopting Bivariate Probit model to address potential bidirectional causality issues arising from “moral hazard.&#x201DResults: The correlation between coverage and health risk is significantly positive, indicating that individuals who exhibit hospitalization behavior are more likely to access PHI. The heterogeneity analysis reveals that adverse selection behavior is more pronounced among individuals characterized by younger age groups and those with better self-rated health. Furthermore, the mechanism analysis found that previously occurring health risks were positively related to the related risks that could occur after enrolling in PHI, with people using past private health risk information to achieve adverse selection.Implication: The unrestricted enrollment of individuals in PHI may result in adverse selection. Insurers engage in introducing risk-adjusted premiums, and designing PHI as a long-term benefit-oriented product may mitigate the likelihood of adverse selection.Keywords: public health insurance, adverse selection, moral hazard, China